Mouse Ocilrp2/Clec2i negatively regulates LPS-mediated IL-6 production by blocking Dap12-Syk interaction in macrophage - Cao, Mingya; Ma, Lina; Yan, Chenyang; Wang, Han; Ran, Mengzhe; Chen, Ying; Wang, Xiao; Liang, Xiaonan; Chai, Lihui; Li, Xia (Frontiers in Immunology, 2022)
C-type lectin Ocilrp2/Clec2i is widely expressed in dendritic cells, lymphokine-activated killer cells and activated T cells. Previous studies have shown that Ocilrp2 is an important regulator in the activation of T cells and NK cells. However, the role of Ocilrp2 in the inflammatory responses by activated macrophages is currently unknown. This study investigated the expression of inflammatory cytokines in LPS-induced macrophages from primary peritoneal macrophages silenced by specific siRNA target Ocilrp2. Ocilrp2 was significantly downregulated in macrophages via NF-κB and pathways upon LPS stimuli or VSV infection. Silencing Ocilrp2 resulted in the increased expression of IL-6 in LPS-stimulated macrophages. Moreover, IL-6 expression was reduced in LPS-induced Ocilrp2 over-expressing iBMDM cells. Furthermore, we found that Ocilrp2-related Syk activation is responsible for expressing inflammatory cytokines in LPS-stimulated macrophages. Silencing Ocilrp2 significantly promotes the binding of Syk to Dap12. Altogether, we identified the Ocilrp2 as a critical role in the TLR4 signaling pathway and inflammatory macrophages' immune regulation, and added mechanistic insights into the crosstalk between TLR and Syk signaling.